ANALISIS FUNGSI NARASI MODEL VLADIMIR PROPP DALAM CERITA WAYANG TOPENG KEDUNG PANJANG KABUPATEN PATI - Angga Krisbianto (COLLASE (Creative of Learning Students Elementary Education), 2023)
This research examines the structure of the Wayang Topeng Kedung Panjang folk story based on Propp's Structural Theory. The Wayang Topeng Kedung Panjang folk story is a story about the love story of Wisnu and Dewi Sri presented through a drama performance where the actors use masks and narrated by a puppeteer. This story is interesting to analyze because the Wayang Topeng Kedung Panjang art is intangible cultural heritage and is one of the extracurricular activities taught in several schools in Pati Regency. This research is a qualitative study using descriptive method, discussing the identification of the function or actions of the characters and classifying the types of characters in the Wayang Topeng Kedung Panjang story. The results of this study found that the Wayang Topeng Kedung Panjang folk story has 14 narrative functions and 5 types of actors.Keywords: function analysis, Vladimir Propp, folk story.